Climatological features of tropical disturbances over the Indian Ocean - south of equator (MAUSAM, 2005)
Based on 17 years (1985 to 2001) of best track data, an attempt has been made to compile the different characteristics viz, genesis, dissipation and movement of tropical disturbances (depression stage onwards) over the Indian Ocean south of equator. These characteristics have been computed over a grid of 2.5° × 2.5° of  Lat./Long. from equator to 40° S and between 35° E to 105° E.The study indicates an interesting feature regarding the formation of cyclone close to equator, between equator to 2.5° S in the month of December 1991. The annual frequency of tropical disturbances has been found to be 11.9 against the climatological normal of 8.4 as given by Gray . Interestingly, no tropical disturbance has been found to dissipate upto 5° S from equator and no disturbance has formed during the period in the latitudinal belt of 27.5° S to 40.0° S. It has been further seen that the frequency of westward (eastward) movement of tropical disturbances decreases (increases) from equator to 2.5° S and 32.5° S to 35.0° S. It is interesting to note that no tropical disturbance has shown eastward movement within equator to 2.5° S.